Juvenile recurrent parotitis: a retrospective comparison of sialendoscopy versus conservative therapy - Schneider, Helgard; Koch, Michael; Künzel, Julian; Gillespie, M. Boyd; Grundtner, Philipp; Iro, Heinrich; Zenk, Johannes (Laryngoscope, 2014)
There are several therapeutic approaches to treat juvenile recurrent parotitis. The aim of this study was to compare sialendoscopy, including prophylactic cortisone irrigation, with observation and a conservative approach of antibiotic therapy alone.Retrospective study, tertiary clinical center.The charts of patients treated for juvenile recurrent parotitis between November 2004 and June 2011 were reviewed. Initial acute flares were always treated with a course of antibiotics. Subsequent treatment consisted of either salivary gland endoscopy including cortisone irrigation or additional pure antibiotic therapy. Patients treated with salivary endoscopy were compared to patients treated with antibiotics alone with regard to the number of inflammatory episodes and pain intensity pre- and posttreatment.Thirty-six patients were treated during the period of study, 15 with salivary endoscopy with cortisone irrigation and 21 with antibiotic therapy alone. A significant reduction in recurrent episodes and pain intensity following therapy was found in both groups. With respect to these two outcomes, the comparison showed two therapeutic options of equal merit.Salivary gland endoscopy is an option in the management of juvenile recurrent parotitis that helps in confirming the diagnosis and that also provides therapeutic intervention. However, although there are further advantages, the definitive value of salivary gland endoscopy requires ongoing evaluation in further prospective studies.4.
EVALuna2:19939